Estratégias de aprendizagem no trabalho: a influência da cultura de inovação - Gimenez, Adriane Barbosa (2020)
In order to maintain competitiveness in the actual world of work, the organization should favor the learning of new skills. In this scenario, where learning plays a key role, Workplace Learning Strategies (WLS) used by employees are presented as an important factor, in order that they are able to keep up with the constant transformations and innovations of the market. In the academic environment, the variable of learning has shown itself as promissory and in a phase of consolidation. The learning process is affected by contextual and individual processes, and in the present study, the focus centers around the variable of innovation culture, which is multidimensional and refers to organizational culture that endorses and supports innovation. In light of the aforementioned, the general objective was to verify the influence of innovation culture on the learning strategies in the workplace. In order to reach the proposed objective, descriptive and quantitative research was performed and an organization was selected through convenience sampling that endorses innovation, which is localized in a municipality of the state of Minas Gerais, and works in the service industry. Questionnaires were distributed among the workers with a return rate of 61% (n=152). In order to measure each of the study variables, measures with evidence of empirical validation were used, with the culture of innovation consisting of 15 factors, and the WLS consisting of five factors, and to provide answers to these a likert response scale was employed of five and 10 points, respectively. The findings from multiple standard regression show that innovation culture was a predictive factor of WLS, where explanatory power was greater for Active Reflection (R2= 30%), with a significant contribution arising from institutional communication factors (beta=0.23;p<0.05) and flexible rules (beta=0.22;p<0.05). The present study contributes to the understanding of WLS predictors and points out that culture of innovation is a relevant factor, but not singular, since it emphasizes the importance of the organizational environment with innovative features. These features become the starting point for generating dialogue and share meanings, thus favoring the use of learning strategies at work in a reflective manner, interpersonal relationships of greater relevance to the development of professionals and consequently the possibility of the organization to administer its competitive advantages. Therefore, work contributes to the efforts of academic research, as well as to organizational practices. Keywords: Learning strategies at work. Learning. Innovation culture.